2016
DOI: 10.1002/joc.4605
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of extreme rainfall events over the Northwest Himalaya using satellite data

Abstract: Using remotely sensed Tropical Rainfall Measuring Mission (TRMM) 3B42 version 7 precipitation data, an investigation on extreme rainfall events (EREs) during the monsoon season has been conducted over the Northwest Himalaya (NWH) for the period of 1998–2013. The satellite precipitation data have been validated with gridded rain gauge data prepared by India Meteorological Department (IMD) using standard statistical measures. A strong positive correlation of 0.88 is found between both, supporting the use of 3B42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 63 publications
(79 reference statements)
2
46
0
Order By: Relevance
“…Based-on this major extreme event analysis, the error statistics indicator showed that TMPA-3B42 performed better against reference IMD data. The underestimation of TMPA-based rainfall over the Mandakini valley was also reported by Mishra and Srinivasan [56] and Bharti et al [57]. The algorithms used for these satellite rainfall products lack regional factors and orographic settings for precipitation estimation and, apparently, the rainfall biases were observed over this highly complex Himalayan region.…”
Section: Discussionsupporting
confidence: 52%
“…Based-on this major extreme event analysis, the error statistics indicator showed that TMPA-3B42 performed better against reference IMD data. The underestimation of TMPA-based rainfall over the Mandakini valley was also reported by Mishra and Srinivasan [56] and Bharti et al [57]. The algorithms used for these satellite rainfall products lack regional factors and orographic settings for precipitation estimation and, apparently, the rainfall biases were observed over this highly complex Himalayan region.…”
Section: Discussionsupporting
confidence: 52%
“…However, the rainfall amount is significantly underestimated by the TMPA product, with the maximum value of 265 mm against the recorded 650 mm. This under-reporting for gridded satellite products versus rain gauges in the ISMR region is a wellknown feature (Rahman et al, 2009;Mishra and Srinivasan, 2013;Kneis et al, 2014;Bharti et al, 2016). The TMPA estimates are verified against the IMD station observations for a baseline quality check.…”
Section: Description Of the Heavy Rainfall Eventmentioning
confidence: 93%
“…TMPA is known to have difficulties properly estimating the magnitude of rainfall in complex, steep terrain, though the new version V7 has improved in this regard [ Bharti et al ., ]. Bharti et al .…”
Section: Methodsmentioning
confidence: 99%